2014
DOI: 10.1111/cogs.12127
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Analogies on Creative Concept Generation: Lessons From anIn VivoStudy in Engineering Design

Abstract: Research on innovation often highlights analogies from sources outside the current problem domain as a major source of novel concepts; however, the mechanisms underlying this relationship are not well understood. We analyzed the temporal interplay between far analogy use and creative concept generation in a professional design team's brainstorming conversations, investigating the hypothesis that far analogies lead directly to very novel concepts via large steps in conceptual spaces (jumps). Surprisingly, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 99 publications
0
69
0
5
Order By: Relevance
“…This can lead to incremental changes that in turn become innovations, or breakthrough ideas (Chan & Schunn, 2014). Empathizing is also a studied approach which, like the use of analogies, provides a means for others to understand the innovation.…”
Section: What Is Creativity?mentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to incremental changes that in turn become innovations, or breakthrough ideas (Chan & Schunn, 2014). Empathizing is also a studied approach which, like the use of analogies, provides a means for others to understand the innovation.…”
Section: What Is Creativity?mentioning
confidence: 99%
“…Since traditional tests are primarily concerned with divergent thinking, some of the more whole-picture creativity measures set forth in the TCT-DP do not have direct links to the traditional measures. As such, Jellen and Bugingo (1989) (Guilford, 1967a;Guilford, Creativity, 1950;Guilford, Three faces of intellect., 1959;Cropley, 2000;Clapham, 1997;Clapham & Schuster, 1992;Runco, Millar, Acar, & Cramond, 2010;Kim, 2011 Need to explore and understand the known and unknown (Harrison, 2016;Hunter, Abraham, Hunter, Goldberg, & Eastwood, 2016;Windahl, 2017;Litman, 2005) Ne New Elements Originality Ability to generate novel ideas (George & Zhou, 2001;Wutrich & Bates, 2001;Furham, 1999;Perrine & Brodersen, 2005;Dollinger, Urban, & James, 2004;Feist, 2010) Ability to coalesce multiple ideas into one (Runco & Nemiro, 1994;Belski, 2009;English, 1997;Lai, Roan, Greenberg, & Yang, 2008;Ozyurt & Ozyurt, 2015;Wakefield, 1985;Rostan, 1994 Capacity for emotional transference (Genco, Johnson, Holtta-Otto, & Conner Seepersad, 2011;Chan & Schunn, 2014;Gardner & Winner, 1982;Piirto, 2004;Kohn, Paulus, & Korde, 2011;Mednick, 1962 Ability to take action in the face of the unknown (Eisenman, 1987;Pankove & Kogan, 1968;Sternberg, 2012;Steele...…”
Section: Evaluating Creativitymentioning
confidence: 99%
“…En outre, les études sur la créativité et les personnalités créatives comprennent aujourd'hui non seulement la catégorie des artistes, des poètes, des romanciers (Patrick, 1937 ;Doyle, 1998) mais aussi les inventeurs et les scientiiques (Chan et Schunn, 2015 ;Hadamard, 1945 ;Weber et Perkins, 1992) sans négliger les personnalités multicréatives, à la fois artistiques et scientiiques.…”
Section: Amalia Dragani Laboratoire D'anthropologie Sociale (Las)unclassified
“…Prior research has found that examples are most inspirational if they are diverse [18,44] and/or appropriate to their current context [18]. Examples can also increase creativity by supporting exploration of iterations and variations on a solution approach [7,27,46], which can lead to not just higher quality [13], but also more novel ideas [35,41]. In contrast, poorly chosen examples can even harm ideation, by inducing distraction [36] or fixation [19,23].…”
Section: Creativity Enhancing Interventionsmentioning
confidence: 99%